Targeting IL-25 as a novel therapy in chronic rhinosinusitis with nasal polyps. Issue 1 (February 2017) - Lee, Mingyu; Kim, Dae Woo; Shin, Hyun-Woo
Abstract : Purpose of review: Chronic rhinosinusitis with nasal polyps (CRSwNP) is a heterogeneous inflammatory disorder with a poorly understood pathophysiology. Recent findings show that epithelial-derived cytokines, including thymic stromal lymphopoietin, IL-33, and IL-25, can exacerbate Th2 immune responses, ultimately leading to recalcitrant chronic rhinosinusitis and nasal polyps. Although IL-25 is increased in CRSwNP, the targeting of IL-25 as a therapeutic strategy remains largely unexplored. In this review, we outline the many recent advances in our understanding of the association between IL-25 and CRSwNP. Recent findings: Recently, we demonstrated that IL-25, produced primarily by sinonasal epithelial cells and infiltrating mast cells, plays an important role in the pathogenesis of CRSwNP in Asian patients. Furthermore, IL-25 and IL-25R are elevated in nasal polyps. This cytokine has roles in the pathogenesis of CRSwNP via modulating group 2 innate lymphoid cells (ILC2s). Similarly, ILC2 enrichment has been reported in CRSwNP patients, and a positive correlation has been shown between ILC2s and CRSwNP. Clinical trials blocking thymic stromal lymphopoietin and IL-33 pathways are ongoing using monoclonal antibodies, AMG157 and AMG282, against CRSwNP, respectively. Summary: Studies on the role played by IL-25 in the pathogenesis of CRSwNP are accumulating and suggest the possibility of a novel therapeutic strategy for treating CRSwNP.